The interaction of Orthoflavivirus nonstructural proteins 3 and 5 with human fatty acid synthase - Suthatta Sornprasert; Wannapa Sornjai; Duncan R. Smith (PLoS ONE, 2025)
Mosquito-transmitted viruses of the genus Orthoflavivirus impose a significant public health burden in many tropical and sub-tropical countries around the world, yet there is still no therapeutic drug to treat infection by any of these viruses, and so a deeper understanding of the mechanism of viral replication is required to identify potential therapeutic targets. Studies have shown that lipid metabolism is modulated upon virus infection, and that fatty acid synthase (FASN) is a key enzyme in fatty acid biosynthesis. In particular it has been reported that FASN interacts with DENV NS3 and is subsequently located to the replication complex. To further investigate this, the interaction of FASN with NS3 and NS5 of the Orthoflaviviruses dengue virus (DENV), Zika virus (ZIKV), and Japanese encephalitis virus (JEV) was investigated by coimmunoprecipitation and indirect immunofluorescent assay. Unexpectedly, FASN interacted with both NS3 and NS5 independently. The colocalization of NS3 and FASN was found for all investigated viruses, and while NS5 interacted with FASN, colocalization was not observed. Markedly however, FASN colocalized with dsRNA, a marker for the replication complex. FASN is an essential enzyme and plays a role in viral replication complex and cellular membrane remodelling. The interaction of FASN with both NS3 and NS5, as well as some of FASN being localized to the site of replication for DENV, JEV and ZIKV further highlights FASN as an important therapeutic target which may have applications to many mosquito-transmitted Orthoflaviviruses.